2011
DOI: 10.2105/ajph.2011.300172
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retail Tobacco Promotions in a Cohort of Stores Before, During, and After a Tobacco Product Display Ban

Abstract: We used a longitudinal design to investigate the impact of a government policy banning the display of tobacco products at the point of sale. The extent of tobacco promotions in 481 randomly selected stores was documented at 4 points in time (2005-2009). Tobacco promotions were greatly reduced after implementation of the display ban. A ban on the display of tobacco products and other signage and promotions at retail is a critical tobacco-control policy to reduce people's exposure to tobacco marketing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…However, compliance was lower than has been found in other jurisdictions, including Victoria, Australia (94.1%),11 Ireland (97%),9 Norway (97%)10 and Ontario, Canada (99.8%) 8. Moreover, we found a substantial proportion of retailers did not comply with other aspects of tobacco retailing laws (excluding sales to minors, which this audit did not assess), with 73.4% failing to comply with at least one aspect of the legislation (table 3).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, compliance was lower than has been found in other jurisdictions, including Victoria, Australia (94.1%),11 Ireland (97%),9 Norway (97%)10 and Ontario, Canada (99.8%) 8. Moreover, we found a substantial proportion of retailers did not comply with other aspects of tobacco retailing laws (excluding sales to minors, which this audit did not assess), with 73.4% failing to comply with at least one aspect of the legislation (table 3).…”
Section: Discussionmentioning
confidence: 60%
“…However, some of those studies have been limited by not including a weighted sample by retailer type,8 and/or by using only urban samples 10 11. There is some evidence that breaches of a display ban are less common than breaches of other retail laws,11 such as restrictions on price boards and requirements for warning signs.…”
Section: Introductionmentioning
confidence: 99%
“…Retailers were already accustomed to retrieval of packs from behind cupboard doors; an audit of tobacco retail outlets has shown that compliance with the requirements of the display ban law has been high in Australia10 as in other countries 11 12. The Australian plain packaging legislation requires that the brand name and variant be printed in a specific font style and the size large enough to be seen by retailers 13.…”
Section: Discussionmentioning
confidence: 99%
“…Case studies in Ireland and Canada show that youth and adult awareness of POS tobacco marketing dropped significantly after a ban on tobacco displays and ads. 17,18 Although these case studies suggest that banning POS tobacco displays and ads could help deter youth smoking, few studies have systematically examined the potential impact of these policies on smoking outcomes.…”
Section: Discussionmentioning
confidence: 99%